PENGARUH CITRA MEREK, KUALITAS PRODUK, HARGA TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK SARIAYU - Ayu Putri Pratiwi (2020)
The rapid competition in the cosmetics industry is characterized by an increase in cosmetics companies, where Indonesia is a fairly large market share. This makes many companies in the cosmetics industry in Indonesia, making it one of the contributing factors in making purchasing decisions. This research proves and analyzes the purchase decision of Sariayu cosmetic is influenced by brand image, quality product, and price. The population in this study are consumer Sariayu. Samples were taken as many as 75 respondents with a random sampling method. The collection of data through the distribution of questionnaires with descriptive and inferential techniques, as well as analytical tools is the SmartPLS3.0 (Partial Least Square) method. The results of this study indicate that the variable brand image and product quality significantly influence purchasing decisions while the price variable does not significantly influence purchasing decisions.